(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article proposes a sensitive and cartographic approach to artistic research grounded in the experience of artistic residencies in mined landscapes. The open-pit mine—understood as both a geological and symbolic space—is conceived as a field of forces, desire, and a symptom of modernity. Through attentive listening to the body, gesture, traces, image, and writing, and by modulating gravities, the research unfolded as a process of folding and reverberation between presence and creation. In doing so, it engages in dialogue with the work of Larrosa, Lepecki, Deleuze, Rolnik, and Kastrup, while considering the ground as a field of instability and the emergence of meaning.